Feodalisme Dalam Wajah Modern: Studi Atas Penguasaan Tanah oleh Korporasi di Indonesia - Siswanto, Heru; Tobing, Clara Ignatia; Maharani, Raden Roro Fadhillah Alifiah; Paruda, Varenzi Tristantino; Hariri, Mohammad Rafiq; Nuraini, Aisyah Afifah; Sari, Dwintya; Pramesti, Salsabila Ayu; Ahma, Caliesta Widi; Tiara, Amanda; Ibrahim, Muhammad; Zakiya, Nathan Luth (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The control of land by large corporations in Indonesia, such as PT Semen Indonesia in Rembang, PT Silva Inhutani Lampung in Mesuji, and PT Perkebunan Nusantara in North Sumatra, reflects a phenomenon of